Heat Transfer Accompanied by Adsorption/Desorption of Water Vapour in Adsorption Heat Pump of Packed Bed Type - Kozuka, Jun; Watabe, Yoshito; Hasatani, Masanobu; Marumo, Chisato; Watanabe, Fujio; Katsuyama, Hitoshi (KAGAKU KOGAKU RONBUNSHU, 1993)
As a step in the application of water vapour adsorption to the heat pump (AHP), the exo - and endothermic characteristics accompanying adsorption/desorption of water vapour in adsorbent packed beds of the external cooling/heating type were studied both experimentally and theoretically. Two adsorbents, structural active carbon and silica gel, which were shown to be usable as the heat storage material in the AHP by experimental results for adsorption equilibrium and rates, were for packed-bed experiments. The trend of experimental results with both adsorbents agrees well with computer simulation under closed -system, one -component, non -isothermal conditions. In addition, the time-changes of amount adsorbed, temperature distributions in the packed bed and periods of adsorption/desorption can be compositely explained by the shape of their isotherms, adsorption/desorption rates and bed density. However, large radial temperature distributions in the direction of the packed bed occur during both the adsorption and desorption processes. This suggests that enhancement of heat transfer in the packed bed is indispensable for this type of AHP.